“Don’t forget the migrants”: exploring preparedness and response strategies to combat the potential spread of MERS-CoV virus through migrant workers in Sri Lanka - Wickramage, Kolitha (F1000Research, 2013)
From September 2012 to July 2013, 81 laboratory-confirmed cases of infection with Middle East respiratory syndrome coronavirus (MERS-CoV), including 45 deaths (a case fatality ratio of 55%) have been reported from eight countries. Human-to-human transmission is now confirmed showing potential for another pandemic of zoonotic disease, with an extremely high mortality rate. Effective surveillance strategies are required in countries with a high influx of migrants from the Middle East to mitigate the probable importation of MERS-CoV. We discuss here the risk of MERS-CoV in major labor sending countries and list the probable strategies for control and prevention of MERS-CoV using Sri Lanka as an example. It is conservatively estimated that 10% of Sri Lanka’s population work as international labor migrants (1.8 to 2 million workers), with 93% residing in the Middle East. An average of 720 workers depart each day, with the majority of these workers (71%) departing to the Kingdom of Saudi Arabia (the country with 81.5% of total MERS-CoV cases). We also describe other inbound migration categories such as tourists and resident visa holders relevant to the context of preparedness and planning. The importance of partnerships between public health authorities at national and regional levels with labor migration networks to establish institutional and/or policy mechanisms are highlighted for ensuring effective preparedness and response planning. Strategies that can be taken by public health authorities working in both labor sending and labor receiving counties are also described.  The strategies described here may be useful for other labor sending country contexts in Asia with a high frequency and volume of migrant workers to and from the Gulf region.